The effects of stroboscopic visual training on human cognitive function and motor performance: a systematic review - Ren, Yinghui; Zhang, Jingfu; Sun, Xiangpeng; Qi, Fengxue; Guo, Feng (Frontiers in Physiology, 2025)
This literature review examines systematically the effects of Stroboscopic Visual Training (SVT) on cognitive function and motor performance in humans with an integrated focus on the underlying neural mechanism. Systematic searches were conducted in major databases, including PubMed and Web of Science, and stringent screening procedures were applied. As a result, 35 high-quality experimental studies were identified and selected for in-depth analysis. The findings indicate that SVT can effectively and significantly enhance the speed of visual information processing and optimize core cognitive functions such as the allocation of attention. In terms of athletic performance, multiple indicators show improvements with enhanced precision in hand-eye coordination and increased motor reaction capabilities. SVT demonstrates consistent and positive effects regardless of athletes’ skill levels. In-depth investigation into its mechanisms reveals that the effects are associated with intermittent visual occlusion, which can induce significant changes in neural plasticity, thereby influencing both cognitive and motor performance. Overall, SVT holds substantial potential as an effective intervention for enhancing cognitive and motor performance. However, current research is limited by insufficient diversity and representativeness in sample selection, a lack of standardized training protocols, and an inadequate exploration of the underlying neural mechanisms. Future studies should aim to optimize experimental design, expand research contexts, and utilize advanced neuroimaging techniques to further elucidate the mechanisms through which SVT exerts its effects. Such efforts will help to unlock the full application value of SVT in fields such as sports training and rehabilitation, providing a more robust scientific foundation for its widespread implementation.